Mud Weight Prediction for Offshore Drilling - Muhamad Faris Bin Ali Osman, Muhamad Faris (Universiti Teknologi Petronas, 2012)
Selecting a proper mud-weight during drilling is important to prevent wellbore breakout. Through development of computer software, the optimum range of mud-weight can be computed by trial-and-error using finite element elasto-plastic model. Even though the results are very accurate and precise, inherited parameter uncertainties associated with the vertical to horizontal earth stress ratios, fracgradients, Coulomb friction angle and cohesion means the precision attained in such software is meaningless and could be misleading to field engineers working on site. An even more pressing problem to the drilling manager is that these software are too specialist oriented and required input parameters that are not available practically in a day-to-day operation to make in-situ decision. The idea behind this project is to propose a new workflow of mud-weight prediction that does not require a precise input of parameters and develop a simple prototype lab-version program that could be used in-house.